2018
DOI: 10.3390/molecules23040965
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Catechins in Cellular Responses to Oxidative Stress

Abstract: Catechins are polyphenolic compounds—flavanols of the flavonoid family found in a variety of plants. Green tea, wine and cocoa-based products are the main dietary sources of these flavanols. Catechins have potent antioxidant properties, although in some cases they may act in the cell as pro-oxidants. Catechins are reactive oxygen species (ROS) scavengers and metal ion chelators, whereas their indirect antioxidant activities comprise induction of antioxidant enzymes, inhibition of pro-oxidant enzymes, and produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
256
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 437 publications
(319 citation statements)
references
References 96 publications
(125 reference statements)
8
256
0
4
Order By: Relevance
“…Accordingly, the heartwood extract used in the present study showed the presence of (−)-EC and (±)-C, as outlined by the quantitative analysis performed. Their pharmacological properties, although much less investigated with respect to EGCG, include the capability of inducing apoptosis [40], an effect strictly linked to their prooxidant activity [41][42][43]. Catechins, as previously outlined, can behave as pro-oxidants in the presence of Cu(II), leading to cytotoxic action [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the heartwood extract used in the present study showed the presence of (−)-EC and (±)-C, as outlined by the quantitative analysis performed. Their pharmacological properties, although much less investigated with respect to EGCG, include the capability of inducing apoptosis [40], an effect strictly linked to their prooxidant activity [41][42][43]. Catechins, as previously outlined, can behave as pro-oxidants in the presence of Cu(II), leading to cytotoxic action [41].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, however, AC treatment did not affect caspase-8's activity, thereby confirming that the apoptosis induced in HT-29 cells was mediated via the intrinsic mitochondrial pathway and not via the extrinsic, death receptor-linked caspase-8 pathway. Finally, even though intrinsic apoptotic signalling is potentially triggered by oxidative stress in many catechin-treated cancer cells [40][41][42][43], the possibility that AC activates apoptosis via a ROS-independent mechanism should be studied further.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress, a condition of disturbance in the balance between the formation of reactive oxygen species (ROS) and the antioxidant defense system, performs as a critical part in the progression of various disease, such as type 2 diabetes, obesity, and cardiovascular disease (Bernatoniene & Kopustinskiene, 2018;Kumar Singh & Patra, 2018). Antioxidant, a kind of substance that protect body cells from harmful oxidative, is demonstrated to reduce the damage of oxidative stress on living tissues, hinder the processes of aging, and prevent the progressions of many diseases from happening (Kim et al, 2017;Zhang, Li, Lin, & Li, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The name catechin derived from the term catechu, the extract of Acacia catechu L. (Braicu, Ladomery, Chedea, Irimie, & Berindan-Neagoe, 2013). The chemical structure is constitued by a FIGURE 3 The chemical structures of (a) quercetin and (b) kaempferol 3,3′,4,5,7-pentahydroxyflavone with two steric forms of (+)-catechin and its enantiomer (Bernatoniene & Kopustinskiene, 2018). Flavanols can form gallic acid conjugates such as epicatechin gallate, epigallocatechin, and epigallocatechin gallate (Braicu et al, 2013;Rosen, 2012).…”
Section: Flavanolsmentioning
confidence: 99%
“…Within nutraceuticals (Andrew & Izzo, ; Daliu, Santini, & Novellino, ; Durazzo & Lucarini, ; Santini et al, ; Santini & Novellino, ; Santini & Novellino, ; Santini, Tenore, & Novellino, ), more than 8,000 different phenolics are identified in the plant kingdom and represent one of most numerous and widely distributed class of plant secondary metabolites (Cheynier, Comte, Davies, Lattanzio, & Martens, ; Kabera, Semana, Mussa, & He, ; Santini, Novellino, Armini, & Ritieni, ). Several outstanding reviews on polyphenols have been recently published (Amiot, Riva, & Vinet, ; Bernatoniene & Kopustinskiene, ; Białecka‐Florjańczyk, Fabiszewska, & Zieniuk, ; Clifford, Jaganath, Ludwig, & Crozier, ; Costa et al, ; Durazzo et al, ; Pervaiz, Songtao, Faghihi, Haider, & Fang, ; Roche et al, ; Xiao, Zhang, Tong, & Shi, ; H. Zhang & Tsao, ; Zhao et al, ), and the reader is referred to them for a more in‐depth information. Here, we provide a concise introductory guide for the beginners in order to assist them in their initial entry into the chemistry and pharmacology of polyphenols.…”
Section: Introductionmentioning
confidence: 99%